Demonstration Gardens in the University of Florida Cooperative Extension Service - Sydney Park Brown; Kim Taylor; Emily Eubanks; Caraline Stephens (EDIS)
UF/IFAS Extension supports a network of demonstration gardens throughout the state. These gardens showcase plants and practices appropriate for their locations and are open to the community free of charge. Learning opportunities abound for home gardeners and landscape professionals on design, planting, and maintenance procedures. The gardens typically have interpretative materials available, including signs, brochures, and self-guided tours. Many are sites for gardening festivals, workshops, and plant sales. This 27-page directory was written by Sydney Park Brown, Kim Taylor, Emily Eubanks, and Caraline Stephens, and published by the UF Department of Environmental Horticulture, June 2014.